2010
DOI: 10.4049/jimmunol.1000719
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Particle-Treated Human Bronchial Epithelial Cells Upregulate Jagged-1 and OX40 Ligand in Myeloid Dendritic Cells via Thymic Stromal Lymphopoietin

Abstract: Ambient particulate matter (PM), including diesel exhaust particles (DEP), promote the development of allergic disorders. Diesel exhaust particles increase oxidative stress and influence human bronchial epithelial cell (HBEC)-dendritic cell (DC) interactions via cytokines including thymic stromal lymphopoietin (TSLP). Upregulation of TSLP results in Th2 responses. Using primary culture human bronchial epithelial cells (pHBEC) and human myeloid DC co-cultures we now show that DEP upregulation of Th2 responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 79 publications
4
63
0
1
Order By: Relevance
“…Furthermore, a co-culture of HBECs with DCs in the presence of DEPs promoted the expression of OX40L and TARC in DCs, and activated DCs subsequently increased the proliferation of T cells. These responses were inhibited by TSLP siRNA transfection to HBECs, which indicated that TSLP produced by HBECs plays a role in the activation of DCs (25,26). A recent study demonstrated that microRNA-375 also regulated DEP-induced but not TNF-a-induced TSLP production in HBECs (27).…”
Section: Diesel Exhaust Particlesmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, a co-culture of HBECs with DCs in the presence of DEPs promoted the expression of OX40L and TARC in DCs, and activated DCs subsequently increased the proliferation of T cells. These responses were inhibited by TSLP siRNA transfection to HBECs, which indicated that TSLP produced by HBECs plays a role in the activation of DCs (25,26). A recent study demonstrated that microRNA-375 also regulated DEP-induced but not TNF-a-induced TSLP production in HBECs (27).…”
Section: Diesel Exhaust Particlesmentioning
confidence: 98%
“…In an experimental asthma model using Dermatophagoides farinae allergens (Der f), the injection of DEPs with Der f enhanced the production of Th2 cytokines, eosinophil infiltration, and airway remodeling (24). Although it has not yet been clarified whether DEP-induced TSLP influences the exacerbation of these allergic manifestations in vivo, Bleck et al reported that DEPs induced TSLP production in human bronchial epithelial cells (HBECs) (25,26). Furthermore, a co-culture of HBECs with DCs in the presence of DEPs promoted the expression of OX40L and TARC in DCs, and activated DCs subsequently increased the proliferation of T cells.…”
Section: Diesel Exhaust Particlesmentioning
confidence: 99%
“…Several recent reports have described experiments using human tissue to investigate mechanisms for diesel effects. In experimental in vitro studies using human bronchial epithelial cells in coculture with myeloid DC, it was reported that diesel exhaust particles induced oxidative stress, which up-regulated epithelial production of thymic stromal lymphopoietin, driving myeloid DC to Th2 polarization (26). Incubation of nonatopic human peripheral blood mononuclear cells with diesel exhaust particlederived polyaromatic hydrocarbons resulted in increased IL-13 and decreased IFN-g production and increased chemotaxis of Th2 lymphocytes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutants can also generate ROS, which activates NF-κB signalling in the airway epithelium, leading to the secretion of the epithelial cytokines IL-1, IL-25, IL-33, GM-CSF, and TSLP, as well as other mediators. Subsequently a variety of cellular events are promoted and result in allergic sensitization to inhaled allergens [124,125]. O 3 [126], NO 2 [127], and cigarette smoke [128,129] induce epithelial cells to release ROS and RNS.…”
Section: Effect Of Air Pollutants On the Airway Epithelium And Respirmentioning
confidence: 99%